1995
DOI: 10.1007/bf00144013
|View full text |Cite
|
Sign up to set email alerts
|

Growth and metastasis of human breast cancers in athymic nude mice

Abstract: To evaluate critically the merit of utilizing a wound model for growing human tumors, a series of increasingly difficult human tumor types were tested for growth at sites of trauma in athymic nude mice. In vitro tumor lines as well as fresh tumors from the breast, colon, rectum, lung, and a metastasis from an unknown primary were intraperitoneally injected into mice subjected to intra-abdominal organ injury. Successful xenografts were obtained from nine of 10 cell lines and 14 of 24 fresh tumors. The latter in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Fifteen patients yielded a stable xenograft (21.4% stable take rate), an approximately 8-fold increase above baseline, and consistent with recently published studies [1, 2, 5, 6, 8-12]. Stable lines represented 12 “triple negative” patients (Table 2), as well as two ER-PR-HER2+ patients (lines BCM-3143/3104 and BCM-3963/4169), and one ER+PR+HER2− patient (line BCM-5097).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Fifteen patients yielded a stable xenograft (21.4% stable take rate), an approximately 8-fold increase above baseline, and consistent with recently published studies [1, 2, 5, 6, 8-12]. Stable lines represented 12 “triple negative” patients (Table 2), as well as two ER-PR-HER2+ patients (lines BCM-3143/3104 and BCM-3963/4169), and one ER+PR+HER2− patient (line BCM-5097).…”
Section: Resultssupporting
confidence: 90%
“…Historically, stable take rates for xenografts were low (~10%, or less), but have improved in more recent studies [1, 2, 5, 6, 8-10, 34-41]. Our stable take rate under condition 2 (estradiol supplementation in SCID/Bg mice) was ~21%, with a statistically similar take rate observed in NSG mice (~19%).…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…Further, once established ER expression can be lost over the course of passaging from mouse to mouse (e.g. [68,57,164], Miragaya et al unpublished), though many current studies have not shown this behavior. These difficulties are offset, in part, by the fact that ER+ cancers account for approximately 75% of all breast cancers, thus offering more opportunities to make successful PDX models.…”
Section: Open Questions Regarding Generation and Use Of Breast Pmentioning
confidence: 98%
“…WOWH mechanism gives another explanation for this phenomenon: there is no correct wound molecular environment in the normal mouse for transplanted cancer cells to respond, while nude mice are partial wounded bodies that some cancer cells with the right activated genes may respond to them. Due to the partial wounded bodies, nude mice do not provide molecules that are suitable for all transplanted cancer cell growth, but the tumor growth may be promoted by providing a wound environment [92, 93]. The use of Matrigel (BD Biosciences) in the transplanted tumor model [94] is an example of such a situation since TGF-β [38], FGF [38], EGF [95], insulin-like growth factor-1 [95], platelet-derived growth factor (PDGF) [96], and nerve growth factor [97] in Matrigel are all actively expressed factors in wounds and they all can activate oncogenes, such as Src [98103], for cancer progress.…”
Section: Applications Of Wowh Mechanismmentioning
confidence: 99%